Expression of HLA system antigens on placenta. - Goodfellow, P; Barnstable, C; Bodmer, W; Snary, D; Crumpton, M (1976)
The levels of HLA-A and -B antigens expressed by placenta have been assessed relative to parental and other A and B antigen types that were not shared by the foetus. A purified preparation of placenta plasma membrane was used to estimate the antigen activities. The results indicate that maternally and paternally inherited A and B antigen activities and beta2-microglobulin are expressed to similar extents but at much lower levels than in spleen lymphocytes (less than 5%). The possibility that the amounts detected were caused by contamination with blood or maternal tissue was ruled out. The low levels of A and B antigens may account for the lack of a cellular immune response to the other polymorphic cell surface antigens of the trophoblast. No evidence was obtained for the expression of a significant level of Ia antigens.